Analyzing Referral Trends in a Child Guidance Clinic: Insights from a Tertiary Care Hospital in Central Maharashtra, India - Mundada, Smita M.; Pawar, Shilpa Y.; Khaire, Prabha (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Background: About 52.9 million children under the age of five have developmental disabilities, with 95% living in low and middle-income countries. The lack of data regarding the burden and risk factors slows the programs and policymaking actions for these highly prevalent conditions in developing countries. The early detection of risk factors and developmental problems can provide faster intervention and, thus, enable a better prognosis. Objectives: This study seeks to analyse the referral profile of developmental disabilities presented to the Child Guidance Clinic (CGC) of a Government Tertiary Care Hospital. Methods: This is a descriptive retrospective study based on medical records of Children presenting with developmental disabilities, irrespective of the cause, between the ages of 1 month and 12 years from November 2016 to December 2018 to a government tertiary care CGC of Maharashtra, India. The patients were enrolled using a convenient sampling method, and data was collected in a pre-designed, validated, structured questionnaire format. Data obtained was compiled on an MS Office Excel sheet and analyzed using SPSS v 26.0 (IBM). Descriptive results of categorical variables are described as frequency (%) and continuous variables as mean ± standard deviation (SD). Results: In this study, 264 cases referred to the CGC were Included and enrolled. The mean age of referral was 2.54 years (±1.00) with an M: F ratio was 1.4:1. Hindu predominance (56.4%) was found in religion. In the record, 76.5% hailed from urban areas; 39% of all cases showed Consanguinity, 37% belonged to Class IV(Upper Lower), and 89% had chronic malnutrition. Additionally, 46.2% of cases had NICU stay, of which perinatal asphyxia (PA) was found in 40%. The majority of children (45.7%) had Global developmental delay (GDD)/Mental Retardation (MR), 37.7% had various forms of CP, Attention Deficit Hyperactivity Disorder (ADHD) was seen in 13%, 3.4% had Autism, 4.5% had specific language disorder, learning disability was seen in 2.7%, and only 2.7% had Isolated motor delay. Conclusions: Early intervention services for children lag in developing countries, and the proportion of children referred to CGC with severe disabling conditions is high. This study's findings highlight a considerable burden and an increasing trend of children being referred for suspected developmental disabilities. This study provides baseline data for further planning services and interventions for these children in Maharashtra.